Using resource allocation for seamless service provisioning in cloud computing - Mustafa Mahmood Akawee; Munef Abdullah Ahmed; Raed Abdulkareem Hasan (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
A Resources allocation is one of the most important things in cloud computing because the environment in which work depends is heterogeneous environment and there are many who request the same service at the same time. Two criteria are used to be considered. First, the time for completing all the required tasks on the available resources and secondly the energy consumed and is extracted from the number of processes that used to complete those tasks. While uploading an application to the Cloud, load balancer allocates the appealed instances for physical computers to balance the computational load of several applications through physical computers. this paper presents some resource allocation problems and issues that can solve with help of load balancing techniques and algorithms. In addition, the performance of the algorithm was measured on seven mathematical functions, and the best results were for the algorithm pyogenes.